Just develop it! : managing the fast-track new product team - Baker, Phil, 1943- (FTPress Delivers elements., 2010)
This Element is an excerpt from From Concept to Consumer: How to Turn Ideas into Money (ISBN: 9780137137473) by Phil Baker. Available in print and digital formats. Don't stop innovating once you've invented a great new product prototype: how to extend innovation throughout the entire process of getting your product to market! Innovation isn't confined to products: you can bring the same level of creativity to the development process, speeding time to market, reducing development costs, and avoiding bureaucratic delays. Why is this important? Because getting to market first with new technology provides a big competitive edge in establishing a brand and maximizing profit...